Promising features of Moringa oleifera oil: recent updates and perspectives. Issue 1 (December 2016) - Nadeem, Muhammad; Imran, Muhammad
Abstract Lipids are the concentrated source of energy, fat soluble vitamins, essential fatty acids, carriers of flavours and many bio-active compounds with important role in maintaining physiological functions of biological body.Moringa oleifera is native to Himalaya and widely grown in many Asian and African countries with seed oil content range from 35–40%.Moringa oleifera oil (MOO) has light yellow colour with mild nutty flavour and fatty acids composition suggests that MOO is highly suitable for both edible and non-edible applications. MOO is extremely resistant to autoxidation which can be used as an antioxidant for the long term stabilization of commercial edible oils. Thermal stability of MOO is greater than soybean, sunflower, canola and cottonseed oils. High oleic contents of MOO are believed to have the capability of increasing beneficial HDL cholesterol and decreased the serum cholesterol and triglycerides. MOO applications have also been explored in cosmetics, folk medicines and skin care formulations. Overall, this review focuses on commercial production status, food applications, antioxidant characteristics, health benefits, thermal stability, fractionation, cholesterol contents, medicinal, nutraceutical action, toxicological evaluation, biodiesel production, personal care formulations and future perspectives of the MOO for the stake holders to process and utilize MOO as a new source of edible oil for industrial purpose.